The dynamics of development of the main types of food and beverage services in the hotel and restaurant entrepreneurship - Boguslavskyi, Oleksandr; Nikitina, Tatyana (My University, 2021)
Сьогодні готельний і ресторанний бізнес повинен працювати в умовах форс-мажору, в умовах пандемії, з постійними обмеженнями діяльності через карантин, введеного штатами. Така ситуація спостерігається в усьому світі. Інноваційним проривом, виходом з цієї непростої ситуації стало активне впровадження комп'ютеризації, інтернет-технологій, онлайн-сервісів, які допомагають існуванню ресторанного бізнесу сьогодні і відкривають нові можливості для просування свого продукту на ринку.Today, the hotel and restaurant business must operate in force majeure, in a pandemic, with constant restrictions on activities due to quarantine imposed by the states. This situation is observed all over the world. An innovative breakthrough, a way out of this difficult situation was the active introduction of computerization, Internet technologies, online services that help the existence of the restaurant business today, and open up new opportunities to promote their product on the market.
Keywords: забезпечення харчуванням готелів; ресторанні послуги; обслуговування в ресторані; restaurant services; hotel catering; кафедра готельно-ресторанної справи